2020
DOI: 10.1021/acs.langmuir.0c00215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser Irradiation on Reversibility and Drug Release of Light-Activatable Drug-Encapsulated Liposomes

Abstract: Although several studies have demonstrated repetitive drug release using light-activatable liposomes, inconsistent drug release at each activation limits widespread usage. Here, we report reversible plasmonic material-coated encapsulated liposomes for proportional controlled delivery of methotrexate (MTX), which is a common drug for cancer and autoimmune diseases, using repetitive laser irradiation. Our results suggest a proportional increase in total drug release after repetitive laser irradiation. We hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…Although the blocking method is an efficient single collision technique for determining the frequency and the height of the current steps during the particle adsorption onto the UME surface [4,14,42,44,45], the reactor method brings more information on the mechanism of the electroporation process and the liposome content release [4,9,15,33,46]. The liposomes size distribution calculated from the charge passed in each current spike (by peak integration) in the i-t curve is a crucial information on the electrolysis process occurring upon impact onto the UME surface.…”
Section: Electrochemical Single Impacts Of Synthetic Redox Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the blocking method is an efficient single collision technique for determining the frequency and the height of the current steps during the particle adsorption onto the UME surface [4,14,42,44,45], the reactor method brings more information on the mechanism of the electroporation process and the liposome content release [4,9,15,33,46]. The liposomes size distribution calculated from the charge passed in each current spike (by peak integration) in the i-t curve is a crucial information on the electrolysis process occurring upon impact onto the UME surface.…”
Section: Electrochemical Single Impacts Of Synthetic Redox Liposomesmentioning
confidence: 99%
“…The liposomes size distribution calculated from the charge passed in each current spike (by peak integration) in the i-t curve is a crucial information on the electrolysis process occurring upon impact onto the UME surface. In this way, several recent investigations deal with the permeability of the liposomes lipid membrane and the effect of the membrane tension on the liposomes content release based on single impact events [9,15,44,46]. Especially, Zhang et al [9] have found that the liposomes electroporation process and the amount of released ferrocyanide content can be controlled by modifying the osmolarity of the buffer in which the 200 nm diameterliposomes are suspended.…”
Section: Electrochemical Single Impacts Of Synthetic Redox Liposomesmentioning
confidence: 99%
“…Our other previous study has also shown that in the longer laser duration, the more drug is released. 26 For the safety of the retina, we calculated maximum permissible exposure based on the following equation.…”
Section: Resultsmentioning
confidence: 99%
“…The laser used in this study was a pulsed picosecond laser with 700 ps pulse duration, 10 kHz repetition frequency at 1064 nm wavelength at 1 W. Although our previous study has shown that drug was released by a single pulse of this laser, 5 s was used per one spot to release physiologically relevant dose in this study. Our other previous study has also shown that in the longer laser duration, the more drug is released . For the safety of the retina, we calculated maximum permissible exposure based on the following equation …”
Section: Discussionmentioning
confidence: 99%
“…Cytosol has a physiological pH value around pH 7.4, whereas the endosome features a pH between 6.5 to 5.0 [10]. The release of the encapsulated contents from liposomes in response to light and temperature needs an additional outer device for their activation [11][12][13][14]. On the other hand, the pH-selective system needs no additional outer device.…”
Section: Introductionmentioning
confidence: 99%